(untitled) (International Journal of Environmental Sciences, 2025)
This paper reviews evidence-based practices for preventing nonventilator hospital-acquired pneumonia (NV-HAP) through oral hygiene interventions. NV-HAP poses a significant risk to patient safety, leading to increased morbidity, mortality, and healthcare costs. The primary aim of this review is to synthesize current research on the effectiveness of various oral care protocols in mitigating the risk of NV-HAP. This study specifically examines interventions such as the use of antimicrobial rinses (e.g., chlorhexidine gluconate), routine tooth brushing, and professional dental care, as well as the implementation of standardized oral care bundles. The methodology involved a comprehensive literature search across multiple databases including PubMed, CINAHL, and Cochrane Library. The search focused on peer-reviewed articles, systematic reviews, and meta-analyses published within the last decade, using keywords such as "nonventilator hospital-acquired pneumonia," "oral hygiene," "chlorhexidine," "hospitalized patients," and "oral care bundles." The inclusion criteria were studies that evaluated the impact of oral hygiene interventions on the incidence of pneumonia in non-ICU, non-mechanically ventilated adult patients. Studies were critically appraised for their methodological rigor, sample size, and clinical outcomes. The results consistently demonstrate a strong correlation between improved oral hygiene and a reduction in NV-HAP rates. The use of 0.12% chlorhexidine gluconate oral rinse was a recurrent and highly effective intervention, particularly when administered twice daily. Studies also highlighted the importance of a multi-component oral care bundle, which typically includes regular tooth brushing, suctioning of oral secretions, and the use of chlorhexidine. The implementation of such bundles has been shown to be more effective than single interventions. Additionally, educational programs for nurses and healthcare staff on the importance and proper technique of oral care were identified as a crucial factor in the successful prevention of NV-HAP. The review found that a lack of standardized protocols and inadequate staff training often contribute to the underutilization of these preventive measures. In conclusion, evidence strongly supports the use of structured, frequent, and multimodal oral hygiene interventions as a cornerstone for preventing NV-HAP. Implementing a standardized oral care bundle that includes regular tooth brushing and the use of antimicrobial rinses, particularly chlorhexidine, can significantly reduce the incidence of pneumonia in hospitalized patients. These practices are low-cost, low-risk, and highly effective in improving patient outcomes and reducing healthcare expenditures. Future research should focus on the long-term sustainability and adherence to these protocols in various hospital settings.